2018
DOI: 10.1029/2018gl079981
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Ice Nucleating Particles Over Southern Ocean Waters

Abstract: A likely important feature of the poorly understood aerosol‐cloud interactions over the Southern Ocean (SO) is the dominant role of sea spray aerosol, versus terrestrial aerosol. Ice nucleating particles (INPs), or particles required for heterogeneous ice nucleation, present over the SO have not been studied in several decades. In this study, boundary layer aerosol properties and immersion freezing INP number concentrations (nINPs) were measured during a ship campaign that occurred south of Australia (down to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
192
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 149 publications
(244 citation statements)
references
References 49 publications
(100 reference statements)
35
192
0
Order By: Relevance
“…PDFs of rainfall rate and DSD parameters (N o * , D m , μ 0 , σ m , and σ' m ) were then analyzed in different latitude bands to identify differences in rainfall properties within the high-latitude bands. The S-highlat and N-polar bands clearly stood out as regions with systematically higher (lower) frequency of occurrence of rainfall rates below (above) 1 mm h −1 , and much lower normalized concentrations N o * , which is consistent with (and therefore possibly linked to) much lower cloud condensation nuclei and ice nucleating particles concentrations observed within pristine high-latitude air masses (e.g., McCluskey et al, 2018). Major differences were also found between latitudes for the μ 0 shape parameter, with high-latitude and midlatitude μ 0 ranging from −1 to +1 and polar and tropical μ 0 ranging from 2 to 5.…”
Section: Discussionmentioning
confidence: 99%
“…PDFs of rainfall rate and DSD parameters (N o * , D m , μ 0 , σ m , and σ' m ) were then analyzed in different latitude bands to identify differences in rainfall properties within the high-latitude bands. The S-highlat and N-polar bands clearly stood out as regions with systematically higher (lower) frequency of occurrence of rainfall rates below (above) 1 mm h −1 , and much lower normalized concentrations N o * , which is consistent with (and therefore possibly linked to) much lower cloud condensation nuclei and ice nucleating particles concentrations observed within pristine high-latitude air masses (e.g., McCluskey et al, 2018). Major differences were also found between latitudes for the μ 0 shape parameter, with high-latitude and midlatitude μ 0 ranging from −1 to +1 and polar and tropical μ 0 ranging from 2 to 5.…”
Section: Discussionmentioning
confidence: 99%
“…Both field studies included measurements of n INPs active at temperatures from 0 to −27 °C using an ice spectrometer (Hiranuma et al, ), which is an off‐line sampling method using collection on open‐faced filters intended to capture the full aerosol size distribution. During the MHD and CAPRICORN study, 27 and 12 samples were collected, respectively, with air sampling durations ranging from 6 to 63 hr (see McCluskey, Ovadnevaite, Rinaldi, et al, and McCluskey, Hill, Humphries, et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…As we show throughout this study, sea spray has a highly nonlinear relationship with wind speed. Given their large contribution to the CCN population (10-65%; Quinn et al, 2017), AOD (Murphy et al, 1998;Revell et al, 2019), and cloud phase (McCluskey et al, 2018) over the Southern Ocean, these particles can have a significant buffering effect on the local climate. We would therefore encourage future studies interested in Journal of Geophysical Research: Atmospheres 10.1029/2019JD032026 climate projections for the Southern Ocean to make use of equation (11) when predicting the surface flux of SSPs.…”
Section: The Direct Radiative Effectmentioning
confidence: 99%
“…Recent studies have also shown that SSPs can act as ice nucleating particles (INPs), which encourage the phase transition of cloud droplets to ice (DeMott et al, ; McCluskey et al, ). Since the Southern Ocean is far removed from continental sources of INPs (e.g., dust), SSPs may be the only source of INPs in the region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation